The ‘Expat’ teacher: an investigation into the motivations and experiences of UK-qualified teachers working in the UAE - Crossley, Adam (2016)
In recent years the number of teachers leaving the teaching profession has risen dramatically. One of the reasons for this is that teachers are being attracted to working overseas at schools offering the British curriculum. The aim of the study was to investigate some of the motivations for teachers wanting to leave the UK and move overseas, what led them to remaining overseas and to look at some of the differences teachers have found between schools at home and abroad. After reviewing the literature on this subject, various themes emerged in general as to why teachers have chosen to make this move. Through comparing these findings with a number of interviews with teachers who have moved to the UAE, the outcomes provided a number of indicating factors relevant to the experiences of teachers who have moved and are working in the UAE.